Rekonstruksi Pengisian Jabatan Sekretaris Desa Dalam Mewujudkan Good Governance: Analisis Hukum Positif Dan Siyasah Dusturiyah - Rooza Meilia Anggraini; Achmad Hasan Basri (Universitas Islam Negeri Islam Kiai Ageng Muhammad Besari Ponorogo, 2026)
Abstract: Village governance requires professional administrative institutions to realize the principles of good governance. However, the prolonged vacancy of the Village Secretary position may reduce administrative effectiveness, legal certainty, and public service quality. This study aims to analyze the practice of filling the Village Secretary position in Sedarat Village, Balong District, Ponorogo Regency from the perspective of Indonesian positive law and to reconstruct an appointment model through the integration of positive law and Siyāsah Dustūriyyah. This research employed doctrinal legal research using statutory, conceptual, and Islamic legal approaches. Legal materials were analyzed through legal interpretation, systematization, and argumentative analysis to evaluate normative compliance and formulate a reconstruction model. The findings reveal that the appointment of an Acting Village Secretary initially complied with applicable regulations; however, the prolonged appointment exceeding the time limit stipulated in the Ponorogo Regency Regulation No. 3 of 2017 contradicts the principles of legal certainty, administrative accountability, professionalism, and effective governance. This study proposes a reconstructed model for filling the Village Secretary position based on five integrated principles: legality, al-kifā'ah (competence), al-amānah (integrity), accountability, and maṣlaḥah (public benefit). The proposed model contributes to strengthening village governance by positioning the appointment of the Village Secretary not merely as an administrative procedure but as a strategic instrument for realizing good governance through the integration of positive law and Siyāsah Dustūriyyah. Keywords: Village Secretary; Good Governance; Village Government; Siyāsah Dustūriyyah. Abstrak: Penyelenggaraan pemerintahan desa memerlukan kelembagaan administrasi yang profesional untuk mewujudkan prinsip-prinsip good governance. Namun demikian, kekosongan jabatan Sekretaris Desa dalam jangka waktu yang berkepanjangan berpotensi menurunkan efektivitas administrasi pemerintahan, kepastian hukum, dan kualitas pelayanan publik. Penelitian ini bertujuan menganalisis praktik pengisian jabatan Sekretaris Desa di Desa Sedarat, Kecamatan Balong, Kabupaten Ponorogo berdasarkan perspektif hukum positif Indonesia serta merekonstruksi model pengisian jabatan melalui integrasi hukum positif dan Siyāsah Dustūriyyah. Penelitian ini merupakan penelitian hukum doktrinal dengan pendekatan perundang-undangan, konseptual, dan Siyāsah Dustūriyyah. Bahan hukum dianalisis melalui teknik interpretasi, sistematisasi, dan argumentasi hukum untuk mengevaluasi kesesuaian praktik pengisian jabatan serta merumuskan model rekonstruksi. Hasil penelitian menunjukkan bahwa pengangkatan Pelaksana Tugas Sekretaris Desa pada tahap awal telah sesuai dengan ketentuan peraturan perundang-undangan. Namun, keberlanjutan status Pelaksana Tugas yang melampaui batas waktu sebagaimana diatur dalam Peraturan Daerah Kabupaten Ponorogo Nomor 3 Tahun 2017 bertentangan dengan prinsip kepastian hukum, akuntabilitas, profesionalitas, dan efektivitas penyelenggaraan pemerintahan. Penelitian ini menawarkan Model Rekonstruksi Pengisian Jabatan Sekretaris Desa Berbasis Legalitas dan Maṣlaḥah yang mengintegrasikan lima prinsip utama, yaitu legalitas, al-kifā'ah (kompetensi), al-amānah (integritas), akuntabilitas, dan maṣlaḥah. Model tersebut menempatkan pengisian jabatan Sekretaris Desa tidak sekadar sebagai pemenuhan prosedur administratif, melainkan sebagai instrumen strategis untuk mewujudkan good governance melalui integrasi hukum positif dan Siyāsah Dustūriyyah Kata Kunci: Sekretaris Desa; Good Governance; Pemerintahan Desa; Siyāsah Dustūriyyah.